San Petersburgo en papel - Ros de Olano, Ignacio (2010)
Comentarios sobre la historia urbana y arquitectónica de la ciudad rusa.
Keywords: RUSIA; ROSSIYA REPUBLIC; SANKT PETERBURG; SAN PETESBURGO; URBANISMO; CIUDADES; ARQUITECTURA; HISTORIA